(untitled) (Research, Society and Development, 2020)
This article deals with Peace Building Circles in public schools. The objective is to understand the types and structure of these Circles in the light of a sociological analysis, in view of the meanings that school subjects attribute to their experiences at school. For this, it is based on the theoretical framework of Elias, Goffman and Weber, from the dialogue with Boyes-Watson and Pranis and other authors relevant to the discussion. It uses semi-structured interviews, discussion groups and direct observation as methodological tools. The results, although not intended to exhaust the discussions, but in order to contribute to the broadening of views within a sociological perspective, show that the types of Peacebuilding Circles instigate different meanings for teachers, students and employees, with organizational structure from which meanings that go beyond a rational explanation. In short, the Circles awaken different perspectives that affect the participants in the school in some way.